(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
At the beginning of COVID-19 pandemic in 2020, the disease was spread across the universe. This virus has level of blistering transmission because it can be transmitted through the air. To contain the outbreak, the people need to be self-isolated to minimize interaction with other people. In this case, the health workers are on the front line to combat this COVID-19 pandemic. It is because they must be dealing with the affected patients directly by taking care of them during their self-isolation period. The health workers must wear personal protective equipment (PPE) to avoid the virus transmission. In this turmoil, the availability of personal protective equipment or PPE is quite worrying. Therefore, the Indonesian government and every government around the world are arm in arm organize a worldwide aid in the form of PPE distribution through referral hospitals, with the objective of making the health workers safer. This research is aimed at conducting a simulation of distribution to obtain PPE route distribution in a more effective and efficient ways to get an optimal route. In this case, this research had been conducted by comparing two methods: saving matrix and tabu search for Hazmat suit distribution. Apart from getting an optimal route, the cost and time could be pushed more effectively to clock the fastest time in distribution with the fewest cost of distribution. The simulation of distribution point used was Distribution Center of West Java as an origin point, specifically at the COVID-19 referral hospitals in West Java, which was listed on the PIKOBAR site as the beneficiary of the PPE and the data of health workers in West Java mentioned in Central Agency on Statistics or locally known as BPS as the determinant of the requested PPE numbers. The result of this research showed that Tabu Search method was more optimal compared to Saving Matrix method based on similar approach, Nearest Neighbor, in determining the route that resulted in four distribution routes. This study showed that Saving Matrix research method concluded a mileage of 2.404 km in 80 hours at the cost of Rp. 10.505.968, while Tabu Search concluded a mileage of 2.351 km in 78 hours at the cost of Rp. 10.437.492.